The Mission of José Mallart as a UNESCO Expert in Ecuador (1957-1959) - Silva Guijarro, Víctor H. (Historia y Memoria de la Educación, 2025)
This article examines the educational work of the Spaniard José Mallart as a UNESCO expert in Ecuador between 1957 and 1959, within the framework of the Technical Assistance Programme. Firstly, it analyses the government of president Galo Plaza and its developmental drive, which laid the foundations for international technical cooperation as a means of educational modernisation. Likewise, it deals with Ecuador’s early links with UNESCO and the implementation of the Technical Assistance Programme, which included –among other activities– the sending of educational missions adapted to local needs to promote educational and social development. The continuity of this programme was supported by the governments of the successive presidents Velasco Ibarra and Ponce Enríquez. Secondly, José Mallart’s mission is studied in detail, with emphasis on his actions in teacher training, applied psychology, career guidance and educational modernisation. Finally, an evaluation of the mission is carried out, highlighting its institutional and pedagogical legacy, its influence on national educational policies and its contribution to educational transformation efforts led by local actors.